Analysis Of Variables Affecting Lecturer Performance - Hidayah, Tamriatin; Sulaksono, Hary (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of psychological contracts, person-organizational fit, and learning agility on lecturer performance. The study was conducted at the Mandala Institute of Technology and Science. The sample was taken from all permanent lecturers. The data analysis method used was multiple linear regression. The results obtained show that: (1) psychological contracts partially influence lecturer performance, (2) person-organizational fit partially influences lecturer performance, (3) learning agility partially influences lecturer performance, and (4) simultaneously, the variables of psychological contracts, person-organizational fit, and learning agility influence lecturer performance.